The Main Prayer Place for Women According to Hadith: Method Analysis al-Jam'u wa al-Tawfiq with Islamic Family Law Approach - M. Jakfar, Tarmizi; bin Adnan, Boihaqi; Sitorus, M. Andreansyah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
The position of women in the hadith has a dignified and equal position among men in worship, social and various other activities. This study aims to discuss the main place of prayer for women according to the hadiths of the Prophet Muhammad PBUH There are two different hadith narrations about the main place of prayer for women, in the mosque or at home. The research method used is qualitative-normative which is analyzed by the method of al-jam'u wa at-tawfiq, which harmonizes different hadiths then studies with the Islamic family law approach. The results showed differences in the history of hadith regarding the main place of prayer for women, the hadith derived from the narration of Aisha allows women in mosques while the hadith narrated by Ibn Umar explains that women are more important at home. As a result, hadith scholars also differ on the main place of prayer, whether in the mosque or at home. If using the method of al-jam'u wa at-tawfiq then this hadith can be compromised, Aisha's narration of allowing women to pray in mosques is when it is safe and does not cause slander. While the narration of Ibn Umar which explains that women are more important to pray at home if there is a concern of interference such as harassment or something dangerous. Some clerics allow prayers in mosques because women do not use fragrances, are not adorned, and must obtain permission from their husbands and guardians. In the perspective of Islamic family law, the prohibition of prayer in the mosque is not absolute, but conditional, women should be protected and treated with dignity and respect, therefore she is protected from slander and all forms of abuse.